2020
DOI: 10.3892/mmr.2020.11006
|View full text |Cite
|
Sign up to set email alerts
|

The roles of mechanosensitive ion channels and associated downstream MAPK signaling pathways in PDLC mechanotransduction

Abstract: The present study aimed to investigate whether the cytoskeleton, the Piezo1 ion channel and the transient receptor potential cation channel subfamily V member 4 (TrPV4) ion channel are equally functional in the mechanotransduction of periodontal ligament cells (Pdlcs) and to reveal the interplay of these mechanically sensitive ion channels (MScs). Human Pdlcs (hPdlcs) were pretreated with cytochalasin d (the inhibitor of actin polymerization), GsMTx4 (the antagonist of Piezo1) and GSK205 (the antagonist of TrP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 55 publications
2
37
0
Order By: Relevance
“…In human epidermal keratinocytes, TRPV4 blocking reduced IL6 and IL8 production caused by gamma irradiation [37]. Additionally, the stretch-induced upregulation of COX2 expression was decreased by treatment with a TRPV4 antagonist in human periodontal ligament cells [38]. The reduction of stretch-induced PGE2 release in the presence of the TRPV4 antagonist further confirms the reduction in COX2 gene expression.…”
Section: Discussionmentioning
confidence: 59%
“…In human epidermal keratinocytes, TRPV4 blocking reduced IL6 and IL8 production caused by gamma irradiation [37]. Additionally, the stretch-induced upregulation of COX2 expression was decreased by treatment with a TRPV4 antagonist in human periodontal ligament cells [38]. The reduction of stretch-induced PGE2 release in the presence of the TRPV4 antagonist further confirms the reduction in COX2 gene expression.…”
Section: Discussionmentioning
confidence: 59%
“…Piezo1 also exists on the membrane of primary PDL cells ( Jin et al, 2015 ). In vitro studies have confirmed that the Piezo1 ion channel can transmit mechanical signals and regulate both the osteogenic differentiation and osteoclastogenesis of PDL cells via various signaling including extracellular regulated protein kinases (ERK), nuclear factor-kappa B (NF-κB), and Notch1 signaling pathways ( Jin et al, 2015 ; Shen et al, 2020 ; Wang et al, 2020a ). These results suggest the possible mechanotransduction role of Piezo1 in the process of OTM.…”
Section: Introductionmentioning
confidence: 99%
“…Ion channels are pore-forming membrane proteins that facilitate direct ion passage through the cell membrane [ 51 ]. Mechanical force-activated ion channels increase membrane permeability and trigger the influx of extracellular calcium, demonstrating their role in mechanotransduction in osteocytes and PDL fibroblasts [ 51 , 128 , 129 ]. Piezo1 ion channel and transient receptor potential cation channel subfamily V member 4 (TRPV4) are key factors in the mechanotransduction of osteocytes and PDL fibroblasts under mechanical loading.…”
Section: Possible Mechanosensorsmentioning
confidence: 99%
“…In vitro mechanical stimulation of mature osteocytes activates Piezo1, which rapidly activates Akt and down-regulates sclerostin [ 131 ]. Piezo1 and TRPV4 increase their expression 8 h after mechanical loading, followed by the increased expression of M-CSF, RANKL and COX2 [ 128 ]. However, pretreatment with the inhibitors of Piezo1 and TRPV4 suppressed the related cytokine expression.…”
Section: Possible Mechanosensorsmentioning
confidence: 99%